2001
DOI: 10.1002/jclp.1131
|View full text |Cite
|
Sign up to set email alerts
|

Brief treatment for elementary school children with disaster‐related posttraumatic stress disorder: A field study

Abstract: Effective psychological intervention is needed to help children recover from disaster-related posttraumatic stress disorder (PTSD). This controlled study evaluated the effectiveness of a brief intervention for disaster-related PTSD. At one-year follow-up of a prior intervention for disaster-related symptoms, some previously treated children were still suffering significant trauma symptoms. Using a randomized lagged-groups design, we provided three sessions of Eye Movement Desensitization and Reprocessing (EMDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
157
1
9

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(174 citation statements)
references
References 22 publications
6
157
1
9
Order By: Relevance
“…However, Eye Movement Desensitisation and Reprocessing (EMDR) holds some promise (Silverman et al, 2008). Of the three controlled studies that support the efficacy of EMDR with children (Ahmad, Larsson, & Sundelin-Wahlsten, 2007;Chemtob, Nakashima, & Carlson 2002;Jaberghaderi, Greenwald, Rubin, Zand & Dolatabadi, 2004), only one involved exposure to a single traumatic event (i.e., hurricane Iniki) (Chemtob et al, 2002). Three uncontrolled group studies (Fernandez, 2007;Oras, De Ezpeleta & Ahmad, 2004;Puffer, Greenwald & Elrod, 1998) and several case reports (Cocco & Sharpe, 1993;Greenwald, 1994;Pellicer, 1993;Tufnell, 2005) have also supported the use of EMDR with child and adolescent populations.…”
Section: Introductionmentioning
confidence: 99%
“…However, Eye Movement Desensitisation and Reprocessing (EMDR) holds some promise (Silverman et al, 2008). Of the three controlled studies that support the efficacy of EMDR with children (Ahmad, Larsson, & Sundelin-Wahlsten, 2007;Chemtob, Nakashima, & Carlson 2002;Jaberghaderi, Greenwald, Rubin, Zand & Dolatabadi, 2004), only one involved exposure to a single traumatic event (i.e., hurricane Iniki) (Chemtob et al, 2002). Three uncontrolled group studies (Fernandez, 2007;Oras, De Ezpeleta & Ahmad, 2004;Puffer, Greenwald & Elrod, 1998) and several case reports (Cocco & Sharpe, 1993;Greenwald, 1994;Pellicer, 1993;Tufnell, 2005) have also supported the use of EMDR with child and adolescent populations.…”
Section: Introductionmentioning
confidence: 99%
“…Only one RCT found that comorbid depression did not improve when PTSD was treated with EMDR, relaxation or biofeedback (Silver, Brooks, & Obenchain, 1995). All of the case studies and case series found an improvement in depressive symptoms when PTSD was successfully treated with EMDR (Chemtob, Nakashima, & Carlson, 2002;Korn & Leeds, 2002;Lobenstine & Courtney, 2013;Montefiore, Mallet, Levy, Allilaire, & Pelissolo, 2007;Raboni, Tufik, & Suchecki, 2006;Schneider et al, 2008;Steven M. Silver, Rogers, & Russell, 2008;Tarquinio, Schmitt, & Tarquinio, 2011;Tarquinio, Schmitt, Tarquinio, Rydberg, & Spitz, 2011). Although each case study on its own is not generalizable due to the nature of the experimental design, the growing number of such reports adds weight to the premise that, in people with PTSD, comorbid depression can be alleviated by treatment with EMDR.…”
Section: Ptsd With Comorbid Depressionmentioning
confidence: 99%
“…The papers are missing the occasional piece of information, such as attrition (Chemtob et al, 2002), equal treatment of the groups (Hogberg et al, 2007), homogeneity of the groups (Ironson et al, 2002) and failure to treat both groups the same during the treatment phase (van der Kolk et al, 2007), but overall there are few concerns about the reports. As is often the case when psychotherapy is compared to a medication regime, in the study by van der Kolk and colleagues, participants in the different groups received different amounts of input from professionals.…”
Section: Ptsd With Comorbid Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although anxiolytic, anticonvulsant, antipsychotic and antidepressant drugs have been tried, none have been consistently associated with improvement [2]. Eye Movement Desensitization Reprocessing (EMDR) is being increasingly utilized as a valid method of treatment for this distressing condition [3][4][5][6][7]. Ego Strengthening (ES) is a sequence of simple psychotherapeutic suggestions given under hypnosis [8].…”
Section: Introductionmentioning
confidence: 99%